(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The study was attempted to explore the small scale broiler farming of Tangail district. Bhuapur, Ghatail, Kalihati, Shakhipur, Delduar and Basail Upazilas were selected purposively for this study. Primary data were collected through face to face interview with the respondents of broiler farmers during February to July, 2016. Secondary data were collected from the BBS, poultry production and marketing reports, journals, DAM, DLS and MS theses. A total of 30 broiler farm owners and 54 intermediaries were selected by applying purposive sampling technique. In the production and marketing system of broiler, many intermediaries were involved such as Bepari, Paiker, Wholesaler and Retailer. Marketing of broiler, produced in Tangail district, was moved from producers to the consumers through four separate chains. The average production cost of farmer for 500 birds was BDT 54781.25, and marketing cost of paiker, wholesaler and retailer were BDT 1230, BDT 1310 and BDT 440, respectively. However, beparies received highest marketing cost which was BDT 1370/500 birds. Transportation was found as the highest cost item which was 37.96%, 39.02% and 40.46%, in case of bepari, paiker, and wholesalers, respectively, but there was no transportation cost of retailer. Broiler farmers sold 90% of their broiler to paiker/bepari and remaining 10% to retailer (distance paiker) sold directly. Paikers sold 85.63% of their broilers to retailers and 14.34% to retailers through wholesalers. Consumer purchases100% of broiler from the retailers in the study areas. Broiler producers did not get fair price due to lack of economic storage facilities, existence of stronger middlemen, inadequacy of veterinary care and services, inefficient transportation facilities, and lack of proper marketing information. It could be concluded that institutional credits, timely supply of inputs and stable price of broiler should be ensured along with the provision of transport and market facilities. Res. Agric., Livest. Fish.7(2): 243-254, August 2020